The environmental impacts of iron and steel industry: a life cycle assessment study. (1st September 2016) - Olmez, Gulnur Maden; Dilek, Filiz B.; Karanfil, Tanju; Yetis, Ulku
Abstract: This study conducts a life cycle assessment for iron and steel production in Turkey using SimaPro software and IMPACT 2002+ impact assessment method with the purpose of comparing the impacts of processes (coke making, sintering, iron making, steel making) and final products (billet, slab, hot rolled wire rod, hot rolled coil), concurrently. System boundary was set as cradle-to-gate and functional unit was selected as 1 ton of final steel product. Among the processes, steel making process exhibited the highest total environmental impact, which was followed by sintering. The highest impacts were in the categories of human health and climate change. Coke production process showed the highest impact on depletion of non-renewable energy sources while it was with a negative contribution in the climate change category because of the avoided external energy consumption due to the production of coke oven gas within the facility. The comparison of the impacts for different final products revealed that hot rolled coil causes the highest total environmental impact followed by hot rolled wire rod, billet and slab. In an attempt to evaluate the effect of having different production scenarios implemented in the facility, three different scenarios representing three different production ratios of semi-finished (billet and slab) and finished (wire rod and coil) products were considered and it was found that the highest impact would come out if all the products were the finished ones and the hot rolling of casting products covers approximately 24% of the total environmental impacts of the full production cycle of one ton of product. Based on the assessment results, suggestions for sustainable production were made. Highlights: Environmental assessment for the integrated iron and steel industry. Products and processes exhibiting the highest total environmental impact. Best opportunities for future impact reduction. The highest impacts are in the categories of human health and climate change. Hot rolled coil causes the highest total environmental impact followed by wire rod, billet and slab.